KALIMAT EFEKTIF RAGAM LISAN KHOTBAH JUMAT DI MASJID JABAL RAHMAH KECAMATAN LANGKAPURA - Nani Angraini (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
This study aims to identify and describe the use of effective sentences in the Indonesian language of the Friday sermon at the Jabal Rahma Mosque, Langkapura District. The method used in this research is descriptive method. Data collection using recording techniques and interviews, the data collected is then analyzed. The content of the sermon is analyzed based on parallels, firmness, frugality, accuracy, cohesiveness, and logic of the sentences in the Friday sermon. The steps taken in analyzing Friday sermons are by transcribing the content of the sermon into written language and identifying sentences in Friday sermons. The results showed that it was quite good in terms of the effectiveness of effective sentences. This can be seen in the cohesiveness, accuracy, and efficiency of the sentence.